A qualitative study of COVID-19 vaccine decision making among urban Native Americans. (December 2022) - Epperson, Anna E.; Carson, Savanna L.; Garcia, Andrea N.; Casillas, Alejandra; Castellon-Lopez, Yelba; Brown, Arleen F.; Garrison, Nanibaa' A.
Abstract: Background: Significant disparities in COVID-19 morbidity and mortality exist for Native American (NA) people, the majority of whom live in urban areas. COVID-19 vaccination is a key strategy for mitigating these disparities; however, vaccination disparities affect NA communities. The current study investigated COVID-19 vaccine decision-making before widespread vaccine rollout occurred, among urban NA communities. We aimed to understand vaccine decision-making factors to develop recommendations about COVID-19 vaccine outreach. Methods: We conducted three in-depth virtual focus groups with 17 NA adults living in an urban community (Los Angeles County) between December 2020 and January 2021. Participants were recruited through NA community-based organizations and community stakeholders. Reflexive thematic analysis was conducted using Atlas.ti. Findings: Participants in this study identified two overarching themes with implications for health vaccination campaigns. First, participants described a need for tailored information and outreach, including NA vaccine outreach that addresses misconceptions about vaccine development to calm fears of experimentation and support communication of vaccine evidence specific to NA people. Second, participants suggested strategies to improve public health resources in the urban NA community, such as the need for unified, proactive communication across trusted NA entities, navigation support to improve vaccine accessibility, and adequately resourcing health partnerships with and among trusted NA community agencies for improved reach. Conclusion: In this qualitative study, we found that urban NA participants reported several factors that affected their vaccine decision-making, including a lack of tailored information for their communities. Our findings also underscore the need to work with tribes, tribal leadership, and urban NA serving organizations to coordinate vaccine communication and distribution to urban communities where the majority of NAs now reside. Further, these findings have implications for COVID-19 vaccine outreach among urban NA communities and demonstrate the need for clear and tailored engagement about the COVID-19 vaccine.